Comparison of Nasopharyngeal Airway Device and Nasal Oxygen Tube in Obese Patients Undergoing Intravenous Anesthesia for Gastroscopy: A Prospective and Randomized Study - Qiansong Xiao; Yingying Yang; Yinbin Zhou; Yan Guo; Xing Ao; Ran Han; Jiali Hu; Dongfeng Chen; Chunhui Lan (Gastroenterology Research and Practice)
Objective. This prospective and randomized study evaluated the efficacy and safety of the nasopharyngeal airway relative to the nasal oxygen tube in obese patients undergoing painless gastroscopy. Materials and Methods. Obese patients (BMI≥28 kg/m2; n=260) were randomly and equally apportioned to the nasopharyngeal airway (Group A) or nasal oxygen tube (Group B) group. Three patients were excluded due to failure of insertion of the nasopharyngeal airway. The duration of endoscopy, anesthetic dose, recovery time, and adverse events were recorded. The satisfaction of the anesthetist, physicians, and patient was scored. Results. The SpO2 reduction was significantly less in Group A than in Group B. Use of a respirator for assisted ventilation occurred significantly less in Group A. The groups were similar regarding mean arterial pressure, heart rate, anesthetic dose, duration of gastroscopy, recovery time, and adverse events. Satisfaction of the physician and anesthetist was greater in Group A; the groups were similar in patient satisfaction. Conclusions. Use of the nasopharyngeal airway for obese patients during painless gastroscopy resulted in less SpO2 reduction relative to the nasal oxygen tube. Altogether, it is a safe and effective device for obese patients undergoing painless gastroscopy.